SISTEM PENDUKUNG KEPUTUSAN KENAIKAN GAJI KARYAWAN MENGGUNAKAN METODE TOPSIS BERBASIS WEB - Syaputra, Wendy; Harman, Rika (Computer Based Information System Journal, 2024)
This research, titled “Decision Support System for Employee Salary Increase Using the TOPSIS Method Based on Web” addresse the issues of non-transparency and subjectivity in determining employee salary increases at Bintang Moro. Fair and objective salary adjustmentsare crucial for retaining and motivating employees, as well as ensuring the company’s sustainability and growth. Decicion support system (DSS) designed in this study uses the TOPSIS method, implemented as a web based application. TOPSIS method was selected for its ability to rank alternatives based ontheir proximity to an ideal solution, ensuring objective decision making.the research involved collecting data on employee performance and salary increases over thepast three months at Bintang Moro. This data was processed using the TOPSIS method and intergrated into a web-based system developed with PHP and Mysql. Finding indicate that the TOPSIS-based DSS provides more objective and transparent recommendations for salary increases. Web-based system also facilitates management in monitoring and evaluating employee performancemore efficiently. The system implementation leads to more equtable salary decisions, fostering a positive work environment. The research contributes to the field by offering a practical solution for decision support in employee salary management. It can serve as a refrence for developing similar system in other organizarional contexrs